Head size in primary total hip arthroplasty. Issue 5 (21st May 2018) - Tsikandylakis, Georgios; Mohaddes, Maziar; Cnudde, Peter; Eskelinen, Antti; Kärrholm, Johan; Rolfson, Ola
Abstract : The use of larger femoral head size in total hip arthroplasty (THA) has increased during the past decade; 32 mm and 36 mm are the most commonly used femoral head sizes, as reported by several arthroplasty registries. The use of large femoral heads seems to be a trade-off between increased stability and decreased THA survivorship. We reviewed the literature, mainly focussing on the past 5 years, identifying benefits and complications associated with the trend of using larger femoral heads in THA. We found that there is no benefit in hip range of movement or hip function when head sizes > 36 mm are used. The risk of revision due to dislocation is lower for 36 mm or larger bearings compared with 28 mm or smaller and probably even with 32 mm. Volumetric wear and frictional torque are increased in bearings bigger than 32 mm compared with 32 mm or smaller in metal-on-cross-linked polyethylene (MoXLPE) THA, but not in ceramic-on-XLPE (CoXLPE). Long-term THA survivorship is improved for 32 mm MoXLPE bearings compared with both larger and smaller ones. We recommend a 32 mm femoral head if MoXLPE bearings are used. In hips operated on with larger bearings the use of ceramic heads on XLPE appears to be safer. Cite this article: EFORT Open Rev 2018;3 DOI: 10.1302/2058-5241.3.170061.